METHODOLOGY OF USING “ZOOLOGY” ELECTRONIC EDUCATIONAL RESOURCE IN TEACHING ZOOLOGY IN HIGHER EDUCATION INSTITUTIONS (Conference Zone, 2022)
In order to effectively organize educational processes in our country, the development of advanced technologies and electronic educational resources, their use, electronic textbooks, the general requirements for their creation, and the differences of electronic textbooks from traditional textbooks are highlighted in the article. In particular, opinions are given about the “Zoology” electronic textbook, its components, and the methodology of its use, developed on the basis of the task of the research work.